2011
DOI: 10.1007/s00436-011-2725-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TLR-2, COX-2, and SOD-2 genes in the peripheral blood leukocytes of opisthorchiasis patients induced by Opisthorchis viverrini antigen

Abstract: Re-infection with liver fluke, Opisthorchis viverrini, increases proinflammatory molecules involved in inflammation-mediated disease and carcinogenesis in an animal model. To clarify whether these genes respond to parasite antigen in peripheral blood leukocytes (PBL) of opisthorchiasis patients, we examined the transcriptional level of oxidant-generating (toll-like receptor 2 (TLR-2), nuclear factor-kappa B (NF-KB), and cyclooxygenase 2 (COX-2)), anti-oxidant-generating (manganese superoxide dismutase 2 (SOD-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…The results of present study showed that the transcripts of both TLR2 and TLR4 gene were increased on day 28 PI, which is interestingly consistent with the increased in cytokines including Th1 and Th2 types immune responses, suggesting that TLR2 and TLR4 might be engaged in the production of cytokines such as IL-4, IL-10, IFN-γ, and TNF-α in mice with C. sinensis infection [36]. In addition, TLR2-mediated immune response via inflammatory/anti-inflammatory cytokines may be involved in the imbalance of oxidants/antioxidants in patients re-infected by O. viverrini [37].…”
Section: Discussionsupporting
confidence: 62%
“…The results of present study showed that the transcripts of both TLR2 and TLR4 gene were increased on day 28 PI, which is interestingly consistent with the increased in cytokines including Th1 and Th2 types immune responses, suggesting that TLR2 and TLR4 might be engaged in the production of cytokines such as IL-4, IL-10, IFN-γ, and TNF-α in mice with C. sinensis infection [36]. In addition, TLR2-mediated immune response via inflammatory/anti-inflammatory cytokines may be involved in the imbalance of oxidants/antioxidants in patients re-infected by O. viverrini [37].…”
Section: Discussionsupporting
confidence: 62%
“…Re-infection of people in endemic areas occurs more likely after praziquantel treatment and frequently leads to periductal fibrosis that governs the pathogenic effects of inflammation and immunity in liver fluke-associated cholangiocarcinogenesis has been recently reviewed ( Yongvanit, Pinlaor & Bartsch, 2012 ). Cellular damage caused by reactive oxygen species (ROS) and reactive nitrogen species (RNS) during chronic infection appears to be a key event which is further enhanced by an imbalanced oxidant/anti-oxidant system during reinfections ( Yongvanit et al, 2012 ). Increase in periductal fibrosis has been shown to be associated with CCA genesis ( Prakobwong et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a significant decrease in the protein expression of manganese-SOD was reported in the cancer cells of CCA tissues, compared with individual normal bile duct cells located in regions adjacent to the tumor (14). Furthermore, the results of our previous study showed that the decreased gene expression of CAT in the peripheral blood leukocytes of patients with opisthorchiasis is induced by Ov antigen (27). Additionally CAT was found to be downregulated in an animal model of opisthorchaiasis-associated CCA, detected via kinetic analysis using the cDNA microarray technique (28).…”
Section: Discussionmentioning
confidence: 96%